A Training Person Need Analysis for Music Teachers Readiness to Teaching Music Vocational for Visually Impaired Student: A Review - Teofilus Seisoria, Manggalagita; Ediyanto, Ediyanto; Safiul Ummah, Umi (Green Publisher Indonesia, 2024)
Music vocational is a programme that provides students with work, networking and learning activities outside of school through music performance or other musical activities that encourage students to gain some experience in a music industry job setting. However, music vocational education is still developing and is currently trying to reach students with special needs through special schools. The standardised skills that are commonly used and developed in society need to be understood and practised by children with special needs, especially the visually impaired students. However, its programme some case not being executed by the relevant teachers background. This study aims to examine the need for relevant music teachers for the implementation of music vocational training programmes in special education settings. Literature study on this study to explain the standard specifications of music vocational education and training teachers and how to implement vocational or specialised music learning for visually impaired students. The qualitative data show that vocational music education requires teachers with at least two years' experience and knowledge of music and the music industry, as well as several strategies for teaching visually impaired students in vocational music programmes that are directed towards self-determination in preparation for possible future careers.